The Influence of Understanding Religious Values on Compliance with State Law among Students at the Al-Musyahadah Islamic Boarding School "Smart House of Indonesia" - Prasetyo, Raka; Rosidin, Utang (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The phenomenon of low legal awareness among the public highlights the importance of examining the role of religious values in shaping legal compliance, particularly within Islamic boarding schools. This study aims to determine the effect of understanding religious values on obedience to state law among students of Pondok Pesantren Al-Musyahadah “Rumah Cerdas Indonesia.” The research employed a quantitative approach using simple linear regression analysis. Data were collected from 120 respondents through a Likert-scale questionnaire and analyzed using validity, reliability, and classical assumption tests. The findings indicate that understanding religious values has a positive and significant effect on obedience to state law, meaning that the better the understanding of religious values, the higher the level of legal compliance.